Leadership and Leadership Styles in Health Sector: A Systematic Review2 - Alp, Servet; Sevim, Ferit (Ordu Üniversitesi, 2024)
The aim of this research is to determine the leadership and leadership styles applied in health institutions between the years 2004-2022. In the study carried out using the PICOS research question strategy, PRISMA protocol principles and the flow chart (Follow Diagram), 4 different databases were scanned with the search formula (different keyword combination) created by the researchers between March 12 and July 09, 2022. taken into consideration. In line with the examinations, it has been found that especially in the last five years, studies on leadership and leadership styles have been concentrated on health workers covering different occupational groups in private, public and university hospitals. It has been determined that different leadership styles such as servant, ethical, toxic, paternalistic, clinical and transformational leadership have been studied. In addition, with these leadership styles; Mostly, the relationship-effect between organizational behavior concepts such as job satisfaction, organizational climate, organizational commitment, job performance, organizational citizenship, motivation levels, error management climate, teamwork attitudes were examined, and it was found that these leadership styles showed significant differences according to some socio-demographic characteristics such as age and gender. has been established. It is recommended to provide trainings or seminars for all employees in all socio-technical organizations where the human element is involved, especially in health institutions, in order for the institution to understand and implement leadership and leadership styles in a richer and clearer way. It is recommended to take evidence-based (systematic and-or meta-analysis results) decisions in the development of policies for the creation of organizational climate (ethical leadership climate, etc.).

Bu araştırmanın amacı, 2004-2022 yılları arasında sağlık kuruluşlarında uygulanan liderlik ve liderlik tarzlarını belirlemektir. PICOS araştırma sorusu stratejisi, PRISMA protokolü ilkeleri ve akış diyagramı (Follow Diagram) kullanılarak yürütülen çalışmada, 12 Mart – 09 Temmuz 2022 tarihleri arasında araştırmacılar tarafından oluşturulmuş arama formülü (farklı anahtar kelimesi kombinasyonu) ile 4 farklı veri tabanı taranmış, yapılan tarama neticesinde 37 çalışma değerlendirmeye alınmıştır. Yapılan incelemeler doğrultusunda özellikle son beş yılda özel, kamu ve üniversite hastanelerinde farklı meslek gruplarını kapsayan sağlık çalışanları üzerinde liderlik ve liderlik tarzlarını kapsayan çalışmaların yoğunlaştığı bulunmuştur. Hizmetkâr, etik, toksik, paternalistik, klinik ve dönüşümcü liderlik gibi farklı liderlik tarzlarının çalışıldığı tespit edilmiştir. Bunun yanında bu liderlik tarzları-stilleri ile; çoğunlukla iş doyumu örgüt iklimi, örgütsel bağlılık, iş performansı, örgütsel vatandaşlık, motivasyon düzeyleri, hata yönetimi iklimi, ekip çalışması tutumları gibi örgütsel davranış kavramları arasındaki ilişki-etki incelenmiş ve bu liderlik tarzlarının yaş, cinsiyet gibi bazı sosyo demografik özelliklere göre anlamlı farklılıkların ortaya koyulduğu saptanmıştır. Sağlık kuruluşları başta olmak üzere insan ögesinin yer aldığı tüm sosyo teknik örgütlerde, liderlik ve liderlik tarzlarının kurum tarafından daha zengin, daha açık bir şekilde anlaşılması ve uygulanabilmesi amacıyla bütün çalışanlara yönelik eğitimler veya seminerler verilmesi önerilmektedir. Örgüt ikliminin (etik liderlik iklimi vb.) oluşturulmasına yönelik politikaların geliştirilmesinde kanıt temelli (sistematik ve-veya meta analiz sonuçları) kararların alınması önerilmektedir.
Sağlık sektöründe liderlik ve liderlik tarzları: Bir sistematik derleme çalışması
Keywords: Health Management; Sağlık Yönetimi [EN] Health Services and Systems (Other); Sağlık Hizmetleri ve Sistemleri (Diğer)